Resilient Control Systems—Basis, Benchmarking and Benefit - Craig Rieger; Kevin Schultz; Thomas Carroll; Timothy McJunkin (IEEE Access, 2021)
Because the research area of resilient control systems was pioneered during the last decade, the basis and benchmarking of resilience have continued to mature to achieve what has long been understood as the ultimate benefit of resilience. However, the automation “ship” has long since sailed on society’s dependence on digital control systems as the basis for all our industries and even the appliances in our homes. While these systems have been in general very reliable and provided for many human and operational efficiencies, the designs were not built on a framework that recognizes and adapts to potential debilitating failures from events such as cyber-attack. In this review, we cover a rapidly maturing framework based upon a disturbance and impact resilience evaluation process that considers both the methodologies for assessing resilience and also how key design principals must be applied within distributed control systems to achieve resilience.